Primary Erythromelalgia in a 12-Year-Old Boy: Positive Response to Sodium Channel Blockers Despite Negative SCN9A Mutations - Jakob, A.; Creutzfeldt, R.; Staszewski, O.; Winterpacht, A.; Berner, R.; Hufnagel, M. (Klinische Pädiatrie, 2012)
Erythromelalgia is a rare disorder characterized by recurrent pain attacks, swelling and redness in the distal extremities. The primary forms of the disorder are caused by mutations in voltage-gated sodium channels. Treatment is difficult and controlled therapeutic studies offer little to no guidance. We report on a 12-year-old boy and his first occurrence of primary erythromelalgia. Genetic findings for mutations in the SCN9A gene, which encodes for the α-subunit of sodium channel NaV1.7, were negative. Although initial treatment with sodium nitroprusside was ineffective, subsequent medication with lidocaine and mexiletine, in combination with gabapentin, was successful. Despite negative findings for mutations in the sodium channels, the use of sodium channel blockers should be considered in these patients.
Keywords: erythromelalgia; voltage-gated sodium channels; sodium nitroprusside; sodium channel blockers; lidocaine; mexiletine